2014
DOI: 10.4103/0976-237x.137914
|View full text |Cite
|
Sign up to set email alerts
|

Dental implant as an option for tooth replacement: The awareness of patients at a tertiary hospital in a developing country

Abstract: Aim:A survey was set out to evaluate the knowledge of patients about tooth replacement as a whole, and assess their awareness of implant-retained prosthesis as an option of tooth replacement.Materials and Methods:Information on sociodemographic characteristics, knowledge about implant-retained tooth as an option for missing tooth replacement, cost implication, source of information and knowledge about other options of tooth replacement were obtained from patients attending the dental clinics of the University … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 12 publications
4
37
1
1
Order By: Relevance
“…Diş eksiklikleriyle ortaya çıkan fonksiyon kaybının tekrar kazandırılması implant uygulamalarının primer hedefleri arasında yer almaktadır. 1 İmplant üstü protezleri hareketli ve kısmi protezlerle karşılaştırdığımızda, çiğneme fonksiyonu açısından üstünlük sağladıkları açıktır. 29,30 Mevcut çalışmamızda elde edilen 8,15 VAS skoru da bu sonucu desteklemektedir.…”
Section: Gereç Ve Yöntemlerunclassified
“…Diş eksiklikleriyle ortaya çıkan fonksiyon kaybının tekrar kazandırılması implant uygulamalarının primer hedefleri arasında yer almaktadır. 1 İmplant üstü protezleri hareketli ve kısmi protezlerle karşılaştırdığımızda, çiğneme fonksiyonu açısından üstünlük sağladıkları açıktır. 29,30 Mevcut çalışmamızda elde edilen 8,15 VAS skoru da bu sonucu desteklemektedir.…”
Section: Gereç Ve Yöntemlerunclassified
“…4 The choice of prosthesis for replacing missing teeth is determined by various factors, such as patient's age, education, gender, medical or psychological conditions, level of income, primarily the number of teeth being replaced, quality of ridge and alveolar bone, patient's choice etc. 5,6 The level of awareness and perceptions among patients toward dental restorations and replacements vary in diff erent cultures and populations. A study done in the Kingdom of Saudi Arabia reported that subjective perceptions of esthetic and functional treatment needs were highly variable among the male patients.…”
Section: Introductionmentioning
confidence: 99%
“…Tooth loss is a common condition which can occur due to dental caries, periodontal disease, facial trauma, endodontic failure, and sometimes by iatrogenic factors. 1 According to the American Association of Oral and Maxillofacial Surgeons, 69% of adults aged 35 to 44 would have lost at least one permanent tooth and adults aged above 70 to 74 years would have lost their entire permanent teeth. 2 The World Health Organization classifies edentulous people as physically impaired due to loss of an important part of their body.…”
Section: Introductionmentioning
confidence: 99%